The Role of Endris Foundation in Supporting Underprivileged Communities in Gerung Subdistrict, West Lombok Regency - Susanti, Afifah Rizqi Aida; Amika Wardana; Budiman; Raohun Sapitri; Dina Sarpina (Warta LPM, 2025)
This study aims to describe the role of Endris Foundation as a community-based social institution in assisting underprivileged communities in Gerung District, West Lombok Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation involving 10 informants, including organizational staff and aid recipients. The findings show that Endris Foundation provides two main types of assistance: material support, such as wheelchairs and food packages, and service-based support through medical accompaniment. The wheelchair aid improved mobility for 10 elderly and disabled recipients, while the medical assistance facilitated access to healthcare services for five families. In addition, food distribution helped reduce household economic burdens. Key challenges included family resistance to medical intervention, lack of transparency regarding beneficiary conditions, and communication gaps with village authorities over activity documentation. This study recommends implementing health education for beneficiary families and establishing formal coordination between the foundation and local government to strengthen collaborative efforts. The findings reinforce the vital role of community-based social institutions in addressing disparities in access to basic public services, particularly in areas with limited infrastructure.